Sistem Pakar Skrining Gejala Gangguan Kepribadian Ambang Menggunakan Metode Certainty Factor - MIftahurrahma Rosyda; Tri Suryo Wahyu Aji (STMIK Budi Darma, 2022)
Borderline Personality Disorder is a type of personality disorder characterized by an overall unstable personality pattern, excessive impulsivity, which often confuses sufferers with their own identity. An expert system is a system developed to assist in making decisions on a particular problem. This expert system aims to help screen symptoms of borderline personality disorder and provide solutions to relieve these symptoms. The method used by the expert system is the certainty factor. The expert system development stage uses the waterfall method and uses the PHP programming language. The results of this study are in the form of an accuracy value of 80% with test data of 10 people, these results are obtained by comparing the results of experts with the results of the system that has been designed